A Brief Assessment for HIV Risk: The TCU HVHP Form. (July 2016) - Rowan, Grace A.; Joe, George W.; Lehman, Wayne E. K.; Knight, Kevin
Targeted HIV screens may help identify some risk-related concerns of drug-using offenders. The present study describes the Texas Christian University HIV/Hepatitis Risk Assessment (TCU HVHP) form, a 19-item self-report instrument measuring HIV and hepatitis risks based on a sample ( N = 1, 056) of offenders in eight prisons. Principal components analysis indicated four scales (Injection Risk, Condom Attitudes, Sex Risk, and AIDS Concern) with reliable psychometric properties with coefficient α reliabilities ranging from .72 to .88. Concurrent validities indicated the four scales were related to motivation for treatment, level of drug use, psychosocial functioning, and criminal thinking, although the patterns varied by gender. The TCU HVHP Form should be attractive to programs needing a brief assessment measuring HIV risk behaviors, attitudes toward condom use, and concerns about acquiring and transmitting HIV.